Analisis Pengendalian Risiko Kredit Macet Dengan Menerapkan Sanksi Adat Pada Lembaga Perkreditan Desa Adat Peneng - Ayu Pita Ari; I Nyoman Putra Yasa (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
AbstrakVillage Credit Institution (LPD) is a microfinance institution that manages funds from village communities which are fully regulated based on rules or awig-awig. However, problems that often occur cannot be avoided in a financial institution. This study aims to find out: (1) what is the cause of unpayable principal and interest installment to the LPD at Desa Adat Peneng and, (2) how is the implementation of the customary sanctions in controlling the risk of bad credit to the LPD at Desa Adat Peneng. This study uses a qualitative method. Data collection is done by means of observation, interviews, and study documentation. The informants of this study were the head of the LPD, the treasurer of the LPD, the head of the internal supervisor and members of the internal supervisor who manage and oversee the management of funds from the village community in the LPD at Desa Adat Peneng. The results of this study indicate that (1) the cause of unpayable principal and interest installment to the LPD at Desa Adat Peneng was the failure of the harvest that occurred in 2017 and 2018 due to irrigation improvements, and the character of the community who was not disciplined in completing installment payments, (2) the application of the customary sanctions in controlling the risk of bad credit to the LPD at Desa Adat Peneng is by applying the perampagan sanction as well as the last customary sanction, which is to be expelled from the customary village. The customary sanctions have been regulated in perarem LPD at Desa Adat Peneng.